Application of regimental therapy sitz bath (aabzan) in various diseases: Unani perspective literature - Farzana, M.U.Z.N.; Tharique, I.A. (University of Jaffna, 2018)
The Unani system of Medicine is one of the oldest systems of Medicine that is practiced in India and all over the world. Ilaj Bil Tadbeer(The Regimenal Therapy) is one of four principles of management in Unani system of Medicine. The eminent Unani scholar, Ibne Sina has mentioned 36 regimes of Ilaj Bil Tadbeer in his famous book "Canon of Medicine". They are Irsale Alaq (Leeching), Fasd (Venesection), Huqna (Enema), Hijamat (Cupping), Dalak (Massage), Riyazat (Exercise), Hammam (Bathing), Nutool (Irrigation), Inkebaab (Inhalation), Takmeed (Fomentation), Aabzan (Sitz Bath), etc. Among these, Aabzan is a novel, simple, safe, cost effective, non-invasive and effectivetreatment for various disorders. Aabzanis a type of bath in which up to umbilicus level body is immersed into plain or medicated water (Joshanda and Khaisanda) used for the therapeutic purpose. The present study is an effort to evaluate the status of description of Aabzan in Unani System of Medicine. The data was collected from the all possible Unani literature through an extensive search to record the information related to Aabzan. The interpretive phenomenological analysis was carried out with the recorded data. The aim of analysis was to generate various themes and presented in different tables which contain indications of Aabzan. The indications with formulations mentioned by Unani physicians shows the wide-ranging use of Aabzanfor the management of various disordersbut it is the time to switch-on to validate the claims of ancient Unani physicians about the effectiveness of Aabzan therapy through evidence based study.
Keywords: Aabzan; Ilaj Bil Tadbeer; Unani System of Medicine; Canon of Medicin